Modeling the proactive driving behavior of connected vehicles : a cell-based simulation approach - Zhu, Feng (2020)
Connected vehicles are able to proactively change speed to adapt to the prevailing traffic condition. Even in the mixed traffic environment, connected vehicles may function as leading vehicles, hence influencing the driving pattern of following nonconnected vehicles. This article proposes a cell-based simulation approach to model the proactive driving behavior of connected vehicles. First, a state variable of connected vehicles is introduced to track the trajectory of connected vehicles. Then the exit flow of cells containing connected vehicles is adjusted to simulate the proactive driving behavior, such that the traffic light is green when the connected vehicle arrives at the signalized intersection. The second part of the article conducts numerical tests to examine the effect of the proactive driving behavior of connected vehicles. Extensive test results consistently show that the presence of connected vehicles contributes significantly to the smoothing of traffic flow and vehicular emission reductions in the network.